Primary intraosseous osteoblastic meningioma. - Budhdeo, S; Ibrahim, R; Hofer, M; Gillies, M (SAGE Publications, 2011)
In this case report, we describe a primary osteoblastic intradiploic meningioma with a clinical and radiological appearance simulating osteoma or fibrous dysplasia.